Navigating Ethical Challenges in Cryptocurrency and Blockchain Technologies - Dondjio, Irenee; Kazamias, Andreas (International Journal of Criminology and Sociology, 2025)
The emergence of blockchain and cryptocurrency technologies has transformed digital ecosystems, introducing opportunities for innovation and efficiency alongside profound ethical challenges. This paper explores key ethical considerations in cryptocurrency and blockchain, including the decentralization of financial systems, the balance between privacy and transparency, the use of blockchain for surveillance, and the socio-economic impacts on vulnerable populations. The authors delve into the contrasting emphasis on ethical considerations for financial solutions deployed in developed and developing countries. The borderless nature of blockchain and cryptocurrencies enables decentralised international transactions while simultaneously introducing specific challenges regarding the definition of applicable law and other jurisdictional legal matters. Through a combination of literature analysis and illustrative case studies, the authors examine the complex ethical dilemmas that accompany these technologies in combination with their actual and perceived links to crime. The findings aim to provide actionable insights for policymakers, industry leaders, and researchers, fostering the responsible and equitable adoption of blockchain and cryptocurrency technologies.